Psychogenic Spasmodic Dysphonia and Psychogenic Dysphagia Following Neck Trauma and Domestic Violence: A Case Report - Rian Kurniawan Laksono; Jessica Karen Roberth; Berlian Larashati (International Journal of Health Engineering and Technology, 2026)
Psychogenic spasmodic dysphonia and psychogenic dysphagia are functional disorders of voice and swallowing in which symptoms are disproportionate to structural findings and closely linked to psychological conflict or trauma. A 35-year-old woman presented with sudden inability to swallow solids, liquids, and saliva, accompanied by severe dysphonia, neck pain, dyspnea, nausea, and vomiting, three days after fever and sore throat. She denied trauma despite mild neck erythema and was treated for suspected epiglottitis with steroids and antibiotics; a nasogastric tube passed easily, arguing against obstruction. After three days, flexible fiber-optic endoscopy showed no inflammation or masses in the nasal cavity, nasopharynx, or oropharynx, while laryngoscopy demonstrated bilateral spasmodic vocal fold movements with incomplete glottic closure and no aspiration. In light of the discrepancy between severe symptoms and normal findings, repeated, supportive interviewing led to disclosure of intimate partner violence involving strangulation, lifting by the neck, and impact against a wall. Antibiotics were stopped, steroids tapered, and psychiatry initiated anxiolytics and counseling, with marked improvement of swallowing and voice within one day and safe discharge. This case underscores the need to consider psychogenic etiologies and domestic violence in acute dysphagia and dysphonia with normal structural evaluation and highlights the importance of trauma-informed, iterative history-taking and multidisciplinary care.